Pemanfaatan Teknologi pada Pemasaran dan Pengelolaan Manajemen Menuju Bumdesa Mandiri di Desa Batuaji Kabupaten Tabanan: Pengabdian - Dwinata JS, I Putu Wahyu; Eka Setiawati, Luh Pande; Putra Nugraha, Dewa Made Dwicky (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program was conducted in Batuaji Village, Kerambitan District, Tabanan Regency, Bali, with the aim of enhancing the managerial capacity and digital marketing capabilities of the village-owned enterprise (BUMDesa) Madyamika Karya. Based on preliminary observations, the BUMDesa faced several challenges, including the absence of Standard Operating Procedures (SOP), limited technological literacy among staff, and the lack of digital promotional media. The method used in this program was a combination of training and mentoring, carried out in three main stages: preparation, implementation, and evaluation. The training focused on two key areas: the importance of SOPs in business management and digital marketing strategies using social media, particularly Instagram. The results showed a significant improvement in participants' knowledge and skills, the establishment of the BUMDesa's official Instagram account, and the development of SOPs for livestock credit distribution. However, some challenges remained, such as limited training time and varying levels of digital literacy among participants. To address this, the service team provided follow-up consultation sessions to ensure sustainable implementation of the strategies introduced.